The Thirty-Second Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2013)

General Consultation and Public Hearings on Bill 60 - The English Speaking Catholic Council (ESCC) (2013)
The English Speaking Catholic Council (ESCC) objects to the proposed “Charter,” Bill 60, on the following grounds: • It threatens to erode the historically and legislatively foundational freedoms of conscience, religion, opinion and expression. These are considered to be “first” freedoms in our society and any trend to dilute or undermine these freedoms must be resisted. • It proposes a secularized society in which religious expression and practice are marginalized. It seeks to reframe the public discussion so that the exercising of Charter-protected rights is to be understood as an imposition upon society which requires the permission of the State. • It muddies the separation of Church and State as it proposes the State has the power to define the nature of religious belief, practice and expression. • In all of the aforementioned points the role of the State is elevated above the proper parameters of a democratically elected and responsible government. The ESCC calls upon the Government of Quebec to withdraw Bill 60.